The effect of limb amputation on standing weight distribution in the remaining three limbs in dogs - Cole, Grayson Lee; Millis, Darryl (Veterinary and Comparative Orthopaedics and Traumatology, 2017)
Despite the fact that limb amputation is a commonly performed procedure in veterinary medicine, quantitative data regarding outcomes are lacking. The intention of this study was to evaluate the effect of limb amputation on weight distribution to the remaining three limbs at a stance in dogs. Ten dogs with a prior forelimb amputation and ten dogs with a prior hindlimb amputation; all of which had no history of orthopaedic or neural disease in the remaining three limbs were included in the study. Standing weight bearing was evaluated with a commercial stance analyzer in all dogs. Five valid trials were obtained and a mean percentage of weight bearing was calculated for each remaining limb. The dogs with a previous forelimb amputation, and also those with a previous hindlimb amputation, had the largest mean increase in weight bearing in the contra -lateral forelimb. In conclusion, proactive monitoring of orthopaedic disease in the contralateral forelimb may be advisable in dogs with a previous limb amputation. In addition, when determining candidacy for a limb amputation, disease of the contralateral forelimb should be thoroughly evaluated.Supplementary Material to this article is available online at https://doi.org/10.3415/VCOT-16-05-0075
Keywords: Gait analysis; amputation; musculoskeletal diseases; dog